Glocalizations of digital nomads - Айгул Насирдинова (Проект Байкал, 2022)
The preferences and semiotic roots of digital nomads are considered, and the current state of globalization processes is characterized. Glocalization is viewed as a new paradigm of architecture that increases the dynamics of mobility and universality in the typological patterns of architecture of urban (global) environment. Objects of digital nomads like “third places”, “virtual fires”, WI-FI in infrastructure as elements of eco-digital cities will need tools similar to the controlled chaos.